Composing authorship teams for health equity: an introduction to the health equity research production model - Dustin T. Duncan (International Journal for Equity in Health)
Abstract Privilege—special advantages, opportunities or honors granted only to specific persons or groups, such as cisgender men—is one of the primary causes of structural inequality and health inequality. More specifically, privilege feeds structural inequities that result in adverse health outcomes disproportionately impacting minoritized and marginalized communities. As structural inequality increases globally, there will undoubtedly be an increase in health inequity; this has driven a commensurate increase in health equity research. The increased focus on health equity may lead to evidence-based policy changes, potentially leading to changes in health and reductions in inequities in health. However, it is not enough to rectify health inequities. This paper introduces the Health Equity Research Production Model (HERPM), designed to promote equity, fairness, and justice in the production of research. While grounded in the fields of public health and health equity research, the model is broadly applicable across disciplines, particularly for researchers and institutions seeking to adopt more equitable research practices. To date, there is no current model in the literature focused on research production, despite its critical role in shaping evidence and determining who benefits from its dissemination. The goal of the Health Equity Research Production Model is to re-orient the field towards accountability for prioritizing equity in academic research in an existing system structured on inequality by centering minoritized and marginalized academic scholars and researchers including to expand pathway to reflect communities in need of research and creating equity in research production while improving the quality of the health equity research produced. The Health Equity Research Production Model focuses on research production using a framework of accountability and aims to remediate the compounded effects of privilege through systems and systems change. It prioritizes equity in the: (1) engagement with and centering of communities studied in research in all phases, (2) identities represented within research teams, (3) consideration of identities and groups awarded research grants, and (4) consideration of identities and groups considered for research products, such as peer-reviewed publications. This multi-component strategy for health equity and inclusive scientific approach–which directly addresses privilege inherent within the existing research production model—aims to deconstruct existing individual systems. This writing highlights the production of research products, which is evidence used in policy-decision making and directly associated with academic research success—compounding benefits bestowed upon non-minoritized and non-marginalized academic scholars and researchers.